Characteristics of forest and land fires in Baluran National Park, Situbondo Regency, East Java. Issue 1 (July 2020) - Maulana, F A; Rushayati, S B; Setiawan, Y
Abstract: Fire events of Baluran National Park occured periodically in the dry season. The impacts of the fires was a changes in physical, chemical and biological aspects of the ecosystem that can be illustrated as the fire severity. Important information for habitat management, is vegetation and air temperature as biological and physical aspects. This study aims to identify burned areas and classes of fire severity and to explain the character of fires based vegetation's aspects and air temperature during the fire periods. The character of the fires was described by analysis of normalized burn ratio (NBR), normalized difference vegetation index (NDVI), and the calculation of air temperature under conditions prefires, postfires, and the delta's value. Burned areas in Baluran National Park were identified as 1798.92 ha which classified into fire severity class as low class (1252.71 ha), medium class (543.79 ha), and severe class (2.43 ha). Savanna has a value of dNDVI of 0.2543 which is caused by logging acacia wood for firewood and dNBR of 0.0677 that indicated by burning by the local people for grass growth as livestock's feed. Changes in the air temperature of the savanna of 8.6 0 C. Increasing of air temperature is followed by decreasing of vegetation index (dNDVI an dNBR), but changes in air temperature tend to follow the dNBR's trend rather than the dNDVI's trend.